The Permian-Triassic Riftogen Rocks in the Norilsk Area (NW Siberian Province): Geochemistry and Their Possible Link with PGE-Cu-Ni Mineralization - Nadezhda Krivolutskaya; Valery Mikhailov; Bronislav Gongalsky; Dmitry Kuzmin; Natalia Svirskaya (Minerals, 2022)
The volcanic rocks in the Vologochan syncline, the Khikey River valley, and Mount Sunduk, within the Norilsk area in the NW Siberian large igneous province, have been studied. They belong to the Ivakinsky, Syverminsky, Gudchikhinsky, Khakanchansky, Nadezhdinsky, Tuklonsky, and Morongovsky Formations. These Formations consist of trachybasalts, picritic basalts and tholeiitic basalts with aphyric and porphyritic textures, and intersertal and poikiloofitic structures. For the first time, we demonstrate the variations in the structure and composition of these Formations along the strike, based on 151 analyses of the major and trace elements in the rocks. The thickness of all the Formations, excepting the Morongovsky, reduce dramatically from the Yenisey–Khatanga trough to the Tunguska syneclise, and they pinch out in the east of the Norilsk area and are attributed to riftogen (rift) basalts. The rock compositions also change in this direction, especially in the Gudchikhinsky and Nadezhdinsky Formations. The two subformations of the Gudchikhinsky formation, the lower and upper, disappear in the east, so the Gudchikhinsky consists only of high-Mg rocks, picritic basalts, and picrites. The composition of the Nadezhdinsky formation varies intensely in its (Gd/Yb)n and (Th/Nb) ratios from the Vologochan syncline to the Khikey River valley. These structural and compositional variabilities differ between the rift formations and the platform ones. Two gabbro–dolerite sills from these areas that are close to the Norilsk and Ergalakh intrusive complexes have been studied. The metal contents in volcanic and intrusive rocks are similar and do not differ from the barren rocks of the South Pyasinsky massif comprising the PGE-Cu-Ni deposits. Only the Gudchikhinsky Formation contains elevated Cu and Ni concentrations. These features and the coinciding spatial distribution of the ore-bearing intrusions and picrites of the Gudchikhinsky rocks in the Norilsk–Igarka paleorift suggest their genetic link. It is proposed that the initial ...